PHYSICAL THERAPY MANAGEMENT OF A PATIENT WITH NONSURGICAL IDIOPATHIC NORMAL PRESSURE HYDROCEPHALUS - Lake, Warren; Jackman, Trent (International journal of physiotherapy, 2020)
Background: The disease, Idiopathic Normal Pressure Hydrocephalus (iNPH), affects the ventricles of the brain, which causes an increase in cerebrospinal fluid pressure and presents with a triad of symptoms: dementia, gait, and urinary disturbances. These symptoms are often reversible with treatment via a surgical shunting procedure; however, not all patients are candidates for this intervention. The purpose of this case report was to examine the benefits of physical therapy treatment for a patient who was not a candidate for surgery. Case Summary: 77-year-old male with a triad of iNPH symptoms and MRI confirmation of diagnosis. 7-month history of progressive decline to the full onset of disease. Non-surgical candidate due to osteoarthritis and cervical flexion posture. PT intervention included gait training with new assistive devices, range of motion (ROM), home exercise prescription development and teaching, body weight supported treadmill training (BWSTT), and forced use techniques such as therapist paced recumbent ergometry. Outcome Measures: The patient was seen for 23 visits in an outpatient physical therapy setting, which improved his cervical ROM, and functional assistance level for walking and transfers, until final visits in an episode of care. Conclusion: Physical Therapy intervention may have reduced patient decline in functional areas addressed by therapy. However, the patient continued to decline in ADLs not addressed by therapy. Additional research is needed to evaluate the efficacy of earlier intervention following diagnosis and physical therapy to address patients who are non-surgical candidates with iNPH.